Households’ Risk Perception and Behavioral Responses to Natech Accidents - Junlei Yu; Ana Maria Cruz; Akihiko Hokugo (International Journal of Disaster Risk Science, 2017)
Abstract This study analyzes data on households’ risk perception and protective behavior following a natural disaster triggered technological accident (Natech accident) that occurred at an industrial park in Sendai during the Great East Japan Earthquake and Tsunami, on 11 March 2011. The results indicate that some households carried out multiple evacuations and that households’ risk perceptions changed throughout the Natech accident evacuation process. Risk perception differed according to household location and demographic characteristics. We also found differences in the protective measures adopted for households in different locations. Specifically, those living closer to the Natech accident tended to evacuate immediately, whereas those living further away tended to shelter in place. Wind direction is discussed as a factor that influences households’ risk perception and evacuation response to a Natech accident. The findings of this study advance knowledge of household behavior in response to a Natech accident and can assist emergency managers in developing strategies for better management of evacuation processes.